The Analysis of Basic Mathematical Skills Among First-Years Physics Department Student of 2023 Cohort - Ahmad Dahlan; Sri Agustini; Muhammad Arief Fitrah Istianto Aslim (ARRUS Journal of Social Sciences and Humanities, 2024)
Students must possess fundamental mathematical abilities to comprehend and utilize the complex mathematical models that are integral to the understanding of physical concepts. The objective of this study is to analyze the basic mathematical skills of the incoming class of 2023 students enrolled in the Physics Education Study Program at FMIPA UNM, with particular attention to the ongoing impact of the global pandemic. A descriptive quantitative approach was employed with a total of 93 research subjects. The data were collected via multiple-choice tests covering five principal areas: series and numbers, algebra, geometry, group data analysis, and mathematical modeling. The results of the study indicated that the mean student score was 11.27 out of a maximum score of 25, which is indicative of a low ability category. 89.02% of students exhibited a lack of proficiency, with only one individual scoring above 16 points. This low ability presents a significant challenge to learning physics, which requires a firm grasp of mathematical concepts to fully comprehend topics such as mechanics, optics, and thermodynamics. Factors such as the suboptimal quality of mathematics instruction at the high school level and student selection methods that are not tailored to the specific demands of the study program contribute to this outcome. This study proposes the implementation of remedial mathematics programs and curriculum enhancements to enhance the fundamental mathematical competencies of physics students.